Early Childhood Empathy Ability of Gadget Users - Damalia Aviani; Yuli Kurniawati Sugiyo Pranoto; Mulawarman Mulawarman (Indonesian Journal of Early Childhood Education Studies, 2024)
The use of early childhood gadgets reaps a lot of attention from various parties because the use of gadgets by early children can adversely affect the ability of early childhood empathy. This study aims of this study is to describe the ability of early childhood empathy gadget users in Banyumanik Village. This study uses qualitative methods using data collection techniques in the form of interviews, observations and documentation. The results of this study explain that excessive use of gadgets by early childhood in Banyumanik village has a negative impact on children's behavior that can be seen from the reaction of children in the form of crying, hitting angry at parents to kick the door when getting a refusal to use gadgets. In addition, early childhood gadget users have less concern. The behavior explains that early childhood gadget users have poor empathy abilities. The role of parents in monitoring the use of early childhood gadgets in Banyumanik village can be said to be lacking. This is because parents are not consistent in supervising and educating early childhood in the use of gadgets so that children have less empathic abilities, for example, children cannot read other people's messages well and are selfish. However, in Banyumanik village there are also parents who are consistent and have a firm stance against the use of early childhood gadgets because they hope their children who are still early can have good empathy skills such as not being selfish. Constraints parents in improving the ability of early childhood empathy gadget users include the availability of time parents supervise the use of gadgets, care and attention to the low early childhood, knowledge of parents related to early childhood empathy skills, video content on social media that set a bad example and the consistent level of parents in supervising as well as educating early childhood gadget users.